A Balancing Act: Modern Equality vs Traditional Nobility in Tonga - Salomon, Tim René (Victoria University of Wellington Law Review, 2009)
The article examines the treatment of commoners and nobles under the Tongan Constitution and ordinary legislation. This paper argues that Tonga fails to meet internationally acknowledged equality standards because "Tongan culture clashes head-on with basic human rights requirements". The article provides some suggestions how to achieve a balance between upholding Tongan culture and traditions and complying with internationally accepted equality standards.